A study of the molecular mechanism of progestin-induced regulation of IL-12 and IL-10 and implications for HIV pathogenesis - Louw, Renate (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.